VEGF, ANGPT1, ANGPT2, and MMP-9 expression in the autologous hematopoietic stem cell transplantation and its impact on the time to engraftment - Nowicki, Mateusz; Wierzbowska, Agnieszka; Małachowski, Roman; Robak, Tadeusz; Grzybowska-Izydorczyk, Olga; Pluta, Agnieszka; Szmigielska-Kapłon, Anna (Annals of hematology, 2017)
As a site of complicated interactions among cytokines, bone marrow niche has been the subject of many scientific studies, mainly in the context of the proteins influencing damage or recovery of endothelium after allogeneic hematopoietic stem cell transplantation (HSCT). In this study, we aimed at exploring mutual correlations of bone marrow niche cytokines involved in the homing and mobilization of hematopoietic stem cells, as well as in angiogenesis. The aim of our study was to evaluate levels of cytokines: VEGF, angiopoietin-1 (ANGPT1), angiopoietin-2 (ANGPT2), and matrix metalloproteinase 9 (MMP-9) during autologous HSCT and to examine their influence on hematological recovery. Forty-three patients with hematological malignancies (33 multiple myeloma, 10 lymphoma) were enrolled in the study. Plasma samples were taken at five time points: before conditioning treatment (BC), on transplantation day (0) and 7 (+7), 14 (+14), and 21 (+21) days after HSCT. The cytokine levels were evaluated by ELISA method. Our study revealed decreased levels of VEGF, ANGPT1, and MMP-9 in the early post-transplant period as compared to the baseline (BC). ANGPT2 was decreased after conditioning treatment, but tended to increase from day +7. On day +7, positive correlations between ANGPT1 level as well as MMP-9 and the time to engraftment were observed. As opposite to ANGPT1, negative correlation between ANGPT2 level on day +7 after HSCT and the time to hematological recovery was noticed. Our study suggests that investigated cytokines are an important part of bone marrow environment and significantly influence the time to engraftment after HSCT.